Assessment of health‐related quality of life in Egyptian HCV‐infected recipients after living donor liver transplantation. Issue 11 (November 2015) - El‐Meteini, Mahmoud; Montasser, Iman Fawzy; El Gendy, Eman; Dabbous, Hany; Hashem, Reem ELS; William, Peter; Bahaa, Mohamed; Sakr, Mohammed Amin
Abstract : Objective: Understanding issues pertaining to quality of life is essential for any disease, particularly in recipients of liver transplantation. The aim of this study was to evaluate the impact of liver transplantation on Egyptian recipients' health‐related quality of life (HRQOL). Methods: A prospective study carried out at the Ain Shams Center for Organ Transplantation (Cairo, Egypt), including 35 recipients for the evaluation of HRQOL using short form 36 score (Arabic version) and Beck Depression Inventory scores pre‐transplantation and 1 and 6 months afterwards. Results: The mean age of the recipients was 49.27 ± 8.16 years. Among them, 17 patients were highly educated. A statistically significant improvement in all dimensions of their HRQOL was observed after liver transplantation. Their physical functioning was 45.00 ± 34.34 before liver transplantation while after 1 and 6 months it was 57.50 ± 20.66 and 74.83 ± 19.27, respectively ( P < 0.001). All 17 patients completed their first year after transplantation, showing a statistically significant improvement in all dimensions of their HRQOL one year after liver transplantation except that in mental health, role limitation due to emotional health emotional and social functioning domains. Conclusion: HRQOL is an important aspect of liver transplantation that should not be neglected.